1995
DOI: 10.3312/jyio1952.27.66
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence That the Bonin Islands "Honeyeater" Is a White-eye

Abstract: Since 1958, Apalopteron familiare has been placed in the Meliphagidae and called the Bonin Islands Honeyeater or Ogasawara Honeyeater. Previously it had been treated as a bulbul, a babbler, a sylviid warbler and a white-eye. Here we present 12S rRNA sequence evidence that shows that Apalopteron is a member of the white-eye family Zosteropidae, closely-related to the Golden White-eye (Cleptornis marchei) of the southern Mariana Islands, which was also misidentified as a honeyeater until its true affinities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…The Kishino-Hasegawa test did not indicate a significant difference between the best maximum-likelihood tree and the maximum-likelihood tree that includes all of the scDNA hybridization constraints. Our study falls in line with others where DNA hybridization and DNA sequence results are in general agreement (31,32).…”
Section: Discussionsupporting
confidence: 82%
“…The Kishino-Hasegawa test did not indicate a significant difference between the best maximum-likelihood tree and the maximum-likelihood tree that includes all of the scDNA hybridization constraints. Our study falls in line with others where DNA hybridization and DNA sequence results are in general agreement (31,32).…”
Section: Discussionsupporting
confidence: 82%
“…A. familiare was described originally by von Kittlitz (1831) as a bulbul (Pycnonotidae), but later was placed variously in Timaliidae (Bonaparte 1854), Sylviidae (Sharpe 1882) and Meliphagidae (Deignan 1958). Recently, Springer et al . (1995) studied the 12S rRNA sequence of this species and showed that A. familiare is a member of the White‐eye family (Zosteropidae).…”
mentioning
confidence: 99%
“…They are known from the Izu Islands and the Volcano Islands, which lie to the north and south of the Bonin Islands, respectively. Thus it was considered unusual that they were absent from the Bonin Islands until the discovery by Springer et al . (1995).…”
mentioning
confidence: 99%
“…Compared with white‐eyes, the bill is strong (Hachisuka 1930, Mees 1969), conical and slightly curved, and has round nasal openings entirely closed posteriorly by an operculum, as in most granivorous passeroid groups, but unlike white‐eyes, which have long, slit‐like nostrils placed below an elongate horizontal operculum. Open nostrils are also seen in the Bonin White‐eye Apalopteron familiare , which may be related to the Golden White‐eye Cleptornis marchei (Springer et al. 1995) or the Stachyris group of babblers (Moyle et al.…”
Section: Resultsmentioning
confidence: 99%